Perceptions of the built environment and their association with objective walkability - Guimarães Silva, Karina (2019)
With the increasing burden of motorized transport, urban qualities have guided researchers to understand the influence of urban form on active travel. One of the strategies to evaluate the built environment is walkability, understood as the extent to which urban form may or may not be conducive to walking. This quality may be analyzed subjectively or objectively, considering perceptions or quantifications of environmental characteristics. Therefore, the general research objective is to analyze perceptions of the built environment related to walkability in a brazilian city. Perceptions were extracted from the Origin-Destination survey carried out for an Urban Mobility Plan of a case study – Rolândia/PR An Index was systematized as an objective and composed walkability measure, by census tracts, and analyzed in map overlays in relation to perceptions through the Kruskal-Wallis statistical procedure. Results indicate that functional, aesthetic and destination perceptions were associated to walkability, while perceptions of safety were less relevant. The study contributes for mobility guidelines in incorporating environmental perceptions as support to active travel to promote the sustainable city.